Links between Chinese vocational school students’ perception of parents’ emotional support and school cooperation climate and their academic performance: The mediating role of school belonging - Liu, Yun-Bo; Hou, Xiao-Yu; Chen, Bin-Bin (Frontiers in Psychology, 2022)
The role of social environmental factors on student academic achievement have been conceptualized from the perspective of the ecological system theory. In the present study, a strengths-based approach derived from the theory of positive youth development was adopted to explore the two favorable aspects of proximal social environments, including parents’ emotional support and school cooperation climate, and to examine how these two factors influence the academic performance among Chinese senior-secondary vocational school students. Participants were 1,940 students (55.4% male) who took part in the Programme for International Student Assessment (PISA) 2018 test from four regions in China. The students completed the questionnaires to assess parents’ emotional support, school cooperation climate, school belonging, and academic performance. By adopting the structural equation model, the results revealed that school belonging fully mediates the association between parents’ emotional support and academic scores, and the association between school cooperation climate and academic scores. In addition, multiple group comparison analyses showed there were some gender differences in the relationships between school cooperation climate and academic performance. The practical significance of the influence of parental support and school cooperation climate on student academic achievement was also discussed.